The Effect of Oxygen Enrichment on Cardiorespiratory and Neuropsychological Responses in Workers With Chronic Intermittent Exposure to High Altitude (ALMA, 5,050 m) - Moraga, Fernando A.; López, Iván; Morales, Alicia; Soza, Daniel; Noack, Jessica (Frontiers in Physiology, 2018)
It is estimated that labor activity at high altitudes in Chile will increase from 60000 to 120000 workers by the year 2020. Oxygenation of spaces improves the quality of life for workers at high geographic altitudes (<5000 m). The aim of this study was to determine the effect of a mobile oxygen module system on cardiorespiratory and neuropsychological performance in a population of workers from Atacama Large Millimeter/submillimeter Array (ALMA, 5050 m) radiotelescope in the Chajnantor Valley, Chile. We evaluated pulse oximetry, systolic and diastolic arterial pressure (SAP/DAP), and performed neuropsychological tests (Mini-Mental State examination, Rey-Osterrieth Complex Figure test) at environmental oxygen conditions (5050 m), and subsequently in a mobile oxygenation module that increases the fraction of oxygen in order to mimic the higher oxygen partial pressure of lower altitudes (2900 m). The use of module oxygenation at an altitude of 5050 m, simulating an altitude of 2900 m, increased oxygen saturation from 84±0.8 to 91±0.8% (p<0.00001), decreased heart rate from 90±8 to 77±12 bpm (p<0.01) and DAP from 96±3 to 87±5 mmHg (p<0.01). In addition, mental cognitive state of workers (Mini-Mental State Examination) shown an increased from 19 to 31 points (p<0.02). Furthermore, the Rey-Osterrieth Complex Figure test (memory) shown a significant increase from 35 to 70 (p<0.0001). The results demonstrate that the use of an oxygen module system at 5050 m, simulating an altitude equivalent to 2900 m, by increasing FiO2 at 28%, significantly improves cardiorespiratory response and enhances neuropsychological performance in workers exposed to an altitude of 5050 m.